2017
DOI: 10.1055/s-0037-1603761
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Estimated Cost of Surgery for Chronic Subdural Hematoma Conducted by the Unified Health System in Brazil (2008–2016)

Abstract: Introduction Chronic subdural hematoma (CSH) is one of the most frequent forms of intracranial hemorrhage. It is a collection of encapsulated, well-delimited fluid and/or coagulated blood in several clotting stages located between the dura mater and the arachnoid mater. Objective To describe the epidemiological aspects of CSH described in the database of the Brazilian Unified Health System (SUS, in the Portuguese acronym) regarding admission numbers, hospitalization expenses, health care profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Between the two time points studied in one paper (1969 and 1983), there was a 250% increase in reported crude incidence of cSDH [15]. This is matched by a repeated study within North Wales which demonstrated an increase in incidence in those over 65 from 8.2 to 48 between 1999 and 2017 [1] as well as studies from both Finland [21] and Brazil [14] where data was available over a 25-and 8-year period, respectively.…”
Section: Systematic Literature Searchmentioning
confidence: 84%
See 3 more Smart Citations
“…Between the two time points studied in one paper (1969 and 1983), there was a 250% increase in reported crude incidence of cSDH [15]. This is matched by a repeated study within North Wales which demonstrated an increase in incidence in those over 65 from 8.2 to 48 between 1999 and 2017 [1] as well as studies from both Finland [21] and Brazil [14] where data was available over a 25-and 8-year period, respectively.…”
Section: Systematic Literature Searchmentioning
confidence: 84%
“…The results in Table 1 Table 1 Published crude estimates of the incidence (per 100,000/year) of chronic subdural haematoma identified through systematic literature search *Indicates that incidence was calculated in those aged 65 or older only. Magalhães [14] could be interpreted as suggesting an increasing incidence over time. Due to the disparate geographic locations of the studies as well as differences in case ascertainment, the potential for confounding of this association is high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a dot (•) indicates that the domain was cited by the article. First author, year Lack of data Data reliability Data accuracy Data integration Truche et al, 2020 5 Do Nascimento, 2022 10 Ferreira, 2018 11 Tonatto-Filho, 2019 12 Olijnyk, 2022 13 Do Nascimento, 2021 14 De Magalhães, 2017 15 De Magalhães, 2019 16 De Magalhães, 2017 17 …”
Section: Resultsmentioning
confidence: 99%